Atmospheric Implications of Large C2‐C5 Alkane Emissions From the U.S. Oil and Gas Industry. Issue 2 (25th January 2019) - Tzompa‐Sosa, Z. A.; Henderson, B. H.; Keller, C. A.; Travis, K.; Mahieu, E.; Franco, B.; Estes, M.; Helmig, D.; Fried, A.; Richter, D.; Weibring, P.; Walega, J.; et al.
Abstract: Emissions of C2 ‐C5 alkanes from the U.S. oil and gas sector have changed rapidly over the last decade. We use a nested GEOS‐Chem simulation driven by updated 2011NEI emissions with aircraft, surface, and column observations to (1) examine spatial patterns in the emissions and observed atmospheric abundances of C2 ‐C5 alkanes over the United States and (2) estimate the contribution of emissions from the U.S. oil and gas industry to these patterns. The oil and gas sector in the updated 2011NEI contributes over 80% of the total U.S. emissions of ethane (C2 H6 ) and propane (C3 H8 ), and emissions of these species are largest in the central United States. Observed mixing ratios of C2 ‐C5 alkanes show enhancements over the central United States below 2 km. A nested GEOS‐Chem simulation underpredicts observed C3 H8 mixing ratios in the boundary layer over several U.S. regions, and the relative underprediction is not consistent, suggesting C3 H8 emissions should receive more attention moving forward. Our decision to consider only C4 ‐C5 alkane emissions as a single lumped species produces a geographic distribution similar to observations. Due to the increasing importance of oil and gas emissions in the United States, we recommend continued support of existing long‐term measurements of C2 ‐C5 alkanes. We suggest additional monitoring of C2 ‐C5 alkanes downwind of northeastern Colorado, Wyoming, and western North Dakota to capture changes in these regions. The atmospheric chemistry modeling community should also evaluate whether chemical mechanisms that lump larger alkanes are sufficient to understand air quality issues in regions with large emissions of these species. Key Points: Oil and gas development is the largest source of ethane and propane in the United States; this sector is the third largest source of C4 ‐C5 alkanes Propane is underpredicted over several U.S. regions Boundary layer enhancements of C2 ‐C5 alkanes mixing ratios are largest over the central United States